Targeting the Brain with Nanomedicine - Rueda, Felix; J. Cruz, Luis (Current Pharmaceutical Design, 2017)
Herein, we review innovative nanomedicine-based approaches for treating, preventing and diagnosing neurodegenerative diseases. We focus on nanoscale systems such as polymeric nanoparticles (NPs), liposomes, micelles and other vehicles (e.g. dendrimers, nanogels, nanoemulsions and nanosuspensions) for targeted delivery of bioactive molecules to the brain. To ensure maximum selectivity for optimal therapeutic or diagnostic results, researchers must employ delivery systems that are non-toxic, biodegradable and biocompatible. This entails: (i) use of “safe” materials, such as polymers or lipids; (ii) targeting to the brain and, specifically, to the desired active site within the brain; (iii) controlled release of the loaded agent; and (iv) use of agents that, once released into the brain, will exhibit the desired pharmacologic activity. Here, we explore the design and preclinical use of representative delivery systems that have been proposed to date. We then analyze the principal challenges that have delayed clinical application of these and other approaches. Lastly, we look at future developments in this area, addressing the needs for increased penetration of the blood brain barrier (BBB), enhanced targeting of specific brain sites, improved therapeutic efficacy and lower neurotoxicity.
Keywords: drug delivery